Inovasi Manajemen Pendidikan dalam Membangun Generasi Unggul di SD Plus Al-Luthfi Purwakarta - Zakiah, Nurfitriani Fitrotu; Darma, Surya Hadi (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
Education management at the elementary school level is a significant effort to improve the quality of education in the face of increasingly fierce competitiveness. This study examines the framework of education management in SD Plus Al-Luthfi Purwakarta, as well as its scope and application. The method used is qualitative research with a case study approach and library research. The results showed that the education management framework at SD Plus Al-Luthfi includes structured planning, implementation, and evaluation. The planning process is carried out through a meeting at the beginning of the school year involving all relevant parties, including the foundation and school committee. In addition, academic and non-academic activities are organized by considering employees' abilities and experience. The scope of education management at SD Plus Al-Luthfi includes various elements, such as budgeting, directing, supervising, and evaluating the program. The study found that the success of education management in this school depends on good collaboration between the principal, the foundation, and all teaching staff. The conclusion of this study emphasizes the importance of implementing effective education management to achieve the goal of quality education. Recommendations are given to improve the management of educational resources so that SD Plus Al-Luthfi can compete with other academic institutions.